Nutritional status and the incidence of chronic diseases in the elderly: an integrative review (Research, Society and Development, 2020)
This article aimed to identify scientific evidence on nutritional status and the incidence of chronic diseases in the elderly. For the selection of the sample, criteria were defined for articles indexed from 2012 to 2020 published in national and international journals. Data collection was performed in the database SCIELO, Pubmed and LILACS using the following descriptors: elderly, nutritional status and chronic disease. The search resulted in 42 articles and after using the inclusion and exclusion criteria, 5 articles remained for analysis, interpretation and discussion. There was a high prevalence of overweight among the elderly, especially among women. It was also found that systemic arterial hypertension was the most prevalent disease. These findings are possibly due to the poor quality of eating habits suggesting a relationship between nutritional status and the incidence of chronic diseases in the elderly. Therefore, the need for the effective implementation of public policies that emphasize the change in habits and lifestyles of the elderly population, including the practice of physical activity associated with the change in eating habits and nutritional monitoring, in order to adapt the practices is emphasized. in the prevention and control of chronic diseases, improving the quality of life of this population segment.